Meta-analysis of rosuvastatin efficacy in prevention of contrast-induced acute kidney injury - Zhang J; Guo Y; Jin Q; Bian L; Lin P (Dove Medical Press, 2018)
Jing Zhang,1 Ying Guo,1 Qi Jin,1 Li Bian,2 Ping Lin3 1Department of Nephrology, China-Japan Union Hospital of Jilin University, Changchun, People’s Republic of China; 2Department of Radiotherapy, The Second Hospital of Jilin University, Changchun, People’s Republic of China; 3Department of Nephrology, The First Hospital of Jilin University, Changchun, People’s Republic of China Background: Contrast-induced nephropathy (CIN) is a complication after the intravascular administration of a contrast medium injection. Previous studies have investigated statins as therapy for CIN due to its positive results in the prevention of contrast-induced acute kidney injury (CI-AKI). Nevertheless, the beneficial effects of rosuvastatin pretreatment in preventing CIN in patients with acute coronary syndromes still remain controversial. In this study, we performed a meta-analysis of randomized controlled trials (RCTs) to evaluate the beneficial impact of rosuvastatin in the prevention of CI-AKI in acute coronary syndrome patients.Methods: PubMed, Embase, and Cochrane library were searched, for RCTs, updated on January 2018. The method was to evaluate rosuvastatin prior to angiography for the prevention of CI-AKI in patients undergoing coronary angiography, of which the main outcome was the incidence of CIN.Results: A total of five RCTs were included in this analysis. Patients treated with rosuvastatin prior to invasive angiography had a significantly lower incidence of CI-AKI than controls (odds ratio [OR]: 0.53, 95% CI: 0.40–0.71, P<0.0001). Moreover, the subgroup analysis also showed that the benefit of rosuvastatin for patients with chronic kidney disease (OR: 0.49, 95% CI: 0.26–0.92, P=0.03) and diabetes mellitus (OR: 0.56, 95% CI: 0.38–0.83, P=0.004) which was consistent in compared with the respective control groups.Conclusion: The findings of this meta-analysis suggest that the preoperative rosuvastatin treatment significantly reduces the risk of renal insufficiency of CIN in at-risk patients with chronic kidney disease or diabetes mellitus. Additional studies are needed to identify at-risk patients, provide optimum dose peri-procedural treatment, and reduce the incidence of CIN. Keywords: contrast-induced nephropathy, coronary angiography, rosuvastatin, meta-analysis